Pengaruh Pemberian Ekstrak Etanol Daun Tapak Liman (Elephantopus scaber L.) Terhadap Kadar LDL (Low Density Lipoprotein) Darah Mencit Putih Jantan - Surya Dharma; Elfia Nasri; Zet Rizal (STIFARM Padang, 2012)
It has been done research about effect of Elephantopus scaber L. leaves’s aethanolic extract on the levels of blood LDL in white male mice. The extract was given orally at the dose of 100, 300 and 900 mg/kg BB once a day for 7, 14 and 21 days. The animals were divided into 5 groups, group I as negative control which was given only the standar food, group II as positive control wich was induced by high fat diet, as for the group III, IV, and V has been given the standar food with fat diet and the Elephantopus scaber L. leaves’s aethanolic extract in the dose varied as mentioned before. In the day of 7th, 14th and 21st, the level of blood LDL was examined for all of the group. The result shows that Elephantopus scaber L. leaves’s aethanolic extract reduce the LDL blood level significantly compare to the positive control (p<0,05) for 14 and 21 days of administration.